2015
DOI: 10.1016/j.scitotenv.2014.12.086
|View full text |Cite
|
Sign up to set email alerts
|

Characterising phosphorus and nitrate inputs to a rural river using high-frequency concentration–flow relationships

Abstract: Characterising phosphorus and nitrate inputs to a rural river using highfrequency concentration-flow relationships.Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. AbstractThe total reactive phosphorus (TRP) and nitrate concentrations of the River Enborne, southern England, were monitored at hourly interval between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
155
2
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(172 citation statements)
references
References 50 publications
14
155
2
1
Order By: Relevance
“…Figure 3 shows the combined effects of climatic alterations (uniform changes in precipitation and temperature) and land use and phosphorus removal strategies on the average phosphorus concentrations of the River Thames at Runnymede, approximately 12 km upstream of the tidal limit. Under current land-use and phosphorus removal mitigation strategies, average phosphorus concentrations range from 0.11 to 0.16 mg L -1 , being inversely proportional to precipitation due to the dominance of sewage effluent inputs at this site (Bowes et al, 2015). When an increase in agricultural land use is applied, the average phosphorus concentration increases up to between 0.15 and 0.18 mg L -1 .…”
Section: Impacts On Phosphorus Concentrationmentioning
confidence: 97%
“…Figure 3 shows the combined effects of climatic alterations (uniform changes in precipitation and temperature) and land use and phosphorus removal strategies on the average phosphorus concentrations of the River Thames at Runnymede, approximately 12 km upstream of the tidal limit. Under current land-use and phosphorus removal mitigation strategies, average phosphorus concentrations range from 0.11 to 0.16 mg L -1 , being inversely proportional to precipitation due to the dominance of sewage effluent inputs at this site (Bowes et al, 2015). When an increase in agricultural land use is applied, the average phosphorus concentration increases up to between 0.15 and 0.18 mg L -1 .…”
Section: Impacts On Phosphorus Concentrationmentioning
confidence: 97%
“…There is, therefore, increasing interest in the use of in-stream high resolution water quality monitoring to assemble higher resolution catchment-scale datasets (e.g. Bowes et al, 2015;Halliday et al, 2012;Jordan et al, 2012;Mellander et al, 2012;Mellander et al, 2014;Outram et al, 2014;Skeffington et al, 2015;Wade et al, 2012), which can be used to understand key catchment processes in terms of hydrology, diffuse pollution transfer and trophic impacts and how these may alter under a changing climate.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the collection and interpretation of high-frequency nitrate data collected using water quality sensors can be used to better quantify nitrate loads to sensitive stream and coastal environments [Ferrant et al, 2013;Bieroza et al, 2014;Pellerin et al, 2014], and provide insights into temporal nitrate dynamics that would otherwise be difficult to obtain using traditional field-based mass balance, solute injection, and/or isotopic tracer studies [Pellerin et al, 2009[Pellerin et al, , 2012Heffernan and Cohen, 2010;Sandford et al, 2013;Carey et al, 2014;Hensley et al, 2014Hensley et al, , 2015Outram et al, 2014;Crawford et al, 2015]. Coupling these measurements with techniques for quantifying water sources and/or flow paths [Gilbert et al, 2013;Bowes et al, 2015;Duncan et al, 2015] provides further opportunity for understanding and managing the drivers of coastal eutrophication.…”
Section: Introductionmentioning
confidence: 99%